2019
DOI: 10.21203/rs.2.17516/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CircRNA_0058063 functions as a ceRNA in bladder cancer progression via targeting miR-486-3p/FOXP4 axis

Abstract: Emerging evidences have uncovered critical regulatory roles of circular RNAs (circRNAs) function as dynamic scaffolding molecules in tumorigenesis and progression. However, the aberrant expression and clinical significance of hsa_circ_0058063 (circRNA_0058063) in bladder cancer (BC) remain poorly understood. circRNA expression was analyzed via a microarray in cancerous tissue and non-carcinoma tissues. Luciferase reporter assays and RNA immunoprecipitation (RIP) were both conducted to uncover the function of c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Research has shown that circ_0058063 expression is upregulated in esophageal squamous cell carcinoma, knocking down its expression can reduce the esophageal squamous cell carcinoma proliferation rate through inhibiting GLUT1 expression [ 4 ]; circ_0058063 is overexpressed in bladder cancer tissues. Knockout of circ_0058063 can markedly reduce bladder cancer cells proliferation and invasiveness, promote cell apoptosis, which may target together with miR-486-3p and inhibit FOXP4 expression, and provide a new target for bladder cancer targeted therapy [ 5 ]. However, the influences of circ_0058063 on malignant phenotype of multiple myeloma cells and its mechanism are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that circ_0058063 expression is upregulated in esophageal squamous cell carcinoma, knocking down its expression can reduce the esophageal squamous cell carcinoma proliferation rate through inhibiting GLUT1 expression [ 4 ]; circ_0058063 is overexpressed in bladder cancer tissues. Knockout of circ_0058063 can markedly reduce bladder cancer cells proliferation and invasiveness, promote cell apoptosis, which may target together with miR-486-3p and inhibit FOXP4 expression, and provide a new target for bladder cancer targeted therapy [ 5 ]. However, the influences of circ_0058063 on malignant phenotype of multiple myeloma cells and its mechanism are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…P < 0.05 was supposed as statistically significant. [14][15][16], but its role in OA keeps unknown. To probe whether CASC19 is altered in OA, RT-qPCR assay was conducted to test CASC19 expression in OA tissues, and the results indicated that CASC19 exhibited higher expression in OA samples (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…With the fast development of science and technology, an increasing number of lncRNAs have been identified as crucial regulators in various diseases [27,28]. CASC19 has been uncovered to be implicated in various cancers [14][15][16], but its function in OA remains indistinct. In this work, CASC19 exhibited higher expression in OA tissues and cell model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is ample evidence to indicate that circRNAs are involved in the regulation of various biological activities of malignant tumors. For example, circRNA_00580631 has been shown to promote tumorigenesis of bladder cancer by sponging miR-486-3p and targeting FOXP4 ( 9 ). circRNA MTO1 inhibits gastric carcinoma progression via targeting the miR-3200-5p/PEBP1 axis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%